THEORETICAL AND METHODICAL ASPECTS OF THE ANALYSIS OF THE WORLD FOOD MARKET - V. Mintusov (Вестник университета)
The article is devoted to theoretical aspects of the analysis of the world food market. The role of mechanisms of state regulation in development of the food markets of foreign countries is shown. A conclusion is drawn on the transformation of the world markets of agricultural raw materials and food at the present stage.